Cesarean-epidemiology in the state of Maranhão, 1996 - Elba Gomide Mochel; Liberata Coimbra; Salvana Maria Figueiredo da Costa (Rev Rene)
This article talks about the cesarian epidemiology evaluation in Maranhão state in 1996 it had as an objective the different parturition’s kinds study, the relations among their social-economics, environmental and institution kind variables and the comparation with other researches results. This is an epidemiologic study whose sample was made by 20 chosen municipals according a sistematic sample with an proportional probability in relation to the municipal’s size, eight municipal sectores were visited, and in each of them eight mother’s interviews with children under 5 years old were made totalizing 1268 interviews. The data collection instrument used was a standarted questionnaire. The results showed that the higest rates of cesarians were in urban areas living groups (26,0%), high scholarship levels (35,3%), low aged women (23,5%) and private services users (47,1%).